Menuju Hari Tua Sejahtera: Pengelolaan Keuangan dan Gaya Hidup Sehat - Wahyudi, Triyono Arief; Iskandar, Donant Alananto (Research and Community Service INSTITUT TEKNOLOGI DAN BISNIS KALBIS, 2023)
The Community Service (PKM) activity partner is the Indonesian Christian Church (GKI) Pulo Mas Jakarta Congregation Council, located at Jalan Batu Wulung No. 20, Kayu Putih, Pulo Gadung, East Jakarta, with a congregation of approximately 335 people. The majority of the congregation is aged 45 and over, consisting of private sector employees and retirees from middle-income backgrounds. Based on observations, the partners' main challenges include low financial literacy for retirement preparation, a lack of financial planning for retirement, and limited knowledge about maintaining health as they age. The PKM activities designed include education and training on intelligent financial management for retirement, creating simple financial plans, and implementing easy-to-implement healthy lifestyles (healthy aging). Implementation methods include lectures, discussions, and hands-on practice. This activity is expected to increase financial independence, awareness of retirement planning, and the ability to maintain the congregation's health sustainably.